The Economic Burden of Epilepsy in Bhutan - Wibecan, Leah (Trop Med Int Health, 2018)
OBJECTIVE: To assess the economic impact of epilepsy in Bhutan, a lower-middle-income country with a universal health care system, but with limited access to neurological care. METHODS: A cross-sectional survey was conducted of patients with epilepsy receiving care at Jigme Dorji Wangchuk National Referral Hospital from January to August, 2016. Data were collected on clinical features of epilepsy, cost of care, impact of epilepsy on school or work, and household economic status of participants and matched comparisons (a sibling or neighbor from a separate household without epilepsy). RESULTS: A total of 172 individuals were included in the study (130 adults and 42 children). One-third of adults and 20 (48%) children had seizures at least once per month. Mean annual direct out-of-pocket costs for epilepsy care was 6,054 BTN (91 USD), of which transportation formed the greatest portion (53%). Direct costs of epilepsy were an average of 3.2% of annual household income. Adults missed 6.8 ± 9.0 days of work or school per year on average, and children missed 18.6 ± 34.7 days of school. Of adult participants, 23 (18%) abandoned employment or school because of epilepsy; among school-age children, seven (18%) stopped school because of epilepsy. Households with a person with epilepsy had lower monthly per-person income (6,434 BTN) than comparison households without epilepsy (8,892 BTN; p = 0.027). SIGNIFICANCE: In this lower-middle-income country, despite universal health care services, households of people with epilepsy face a significant economic burden. Cost of transportation for epilepsy care contributes a major proportion of the direct cost burden. Indirect costs, including negative effects on school achievement and employment, disrupt the economic potential of people with epilepsy in Bhutan. Household economic well-being is impacted by the direct and indirect costs of epilepsy.